The vaccinia virus A56 protein: a multifunctional transmembrane glycoprotein that anchors two secreted viral proteins - DeHaven, Brian C. (Society for General Microbiology, 2011)
The vaccinia virus A56 protein was one of the earliest-described poxvirus proteins with an identifiable activity. While originally characterized as a haemagglutinin protein, A56 has other functions as well. The A56 protein is capable of binding two viral proteins, a serine protease inhibitor (K2) and the vaccinia virus complement control protein (VCP), and anchoring them to the surface of infected cells. This is important; while both proteins have biologically relevant functions at the cell surface, neither one can locate there on its own. The A56–K2 complex reduces the amount of virus superinfecting an infected cell and also prevents the formation of syncytia by infected cells; the A56–VCP complex can protect infected cells from complement attack. Deletion of the A56R gene results in varying effects on vaccinia virus virulence. In addition, since the gene encoding the A56 protein is non-essential, it can be used as an insertion point for foreign genes and has been deleted in some viruses that are in clinical development as oncolytic agents.